THE RIGHT TO EDUCATION AS A CONTROL MECHANISM: REFLECTIONS ON SCHOOL IN PRISON - Mauro de Oliveira Braz, José; Ramos de Farias, Francisco (LINKSCIENCEPLACE, 2026)
This paper presents a theoretical reflection on one of the school's use of possibilities within the prison system. Through the presentation of data and theoretical approaches related to education in the prison environment, we intend to demonstrate that although education for the prisoner be a right, it may be able to perform other functions that go beyond compliance with the state constitutional duty to ensure education for all. Therefore, it is necessary to go part of the history of seclusion spaces and isolation, so that, through a socio-historical approach, we can achieve today, in terms of guaranteeing the rights of the arrested student.